Trust in online hotel reviews across review content and hotel category - Chin, Kah Mun (2020)
This research study how consumers’ view towards online hotel reviews is associated with users’ trust across review content and hotel category. Consumers’ view for the three review contents which are review date, review length, and review attachment across with the hotel category that classified by budget hotel and luxury hotel was study in the research. Data collection was originated from a simulation website where created for the consumers to check out when they are planning to go on a trip. The simulation website consists of the reviews for luxury hotel and budget hotel which included all the review contents study in this paper. One hundred respondents had been invited to answer the survey questions based on the reviews in the simulate website. The Statistical Package for Social Science (SPSS) is applied to analyze the data which have been collected.